Serum isolevuglandin IgG antibody concentrations are increased in patients with systemic lupus erythematosus and associated with lower 24-hour blood pressure - Phothisane, Anastasiia; Oeser, Annette M.; Shaik, Shahensha; Wu, Qiong; Posey, Olivia; Davies, Sean S.; Krishnan, Jaya; Patrick, David M.; Stein, C. Michael; Ormseth, Michelle J. (Frontiers in Lupus, 2024)
Objective: Hypertension is frequent in patients with systemic lupus erythematosus (SLE) and is a major contributor to increased cardiovascular risk. Isolevuglandins (IsoLGs) are downstream products of oxidative stress that drive hypertension and SLE disease activity in animal models.Antibodies to IsoLGs (anti-IsoLGs) are present in human SLE and associated with disease activity, but it is not known if concentrations are higher compared to control subjects or if they are associated with blood pressure (BP).We measured serum anti-IsoLG IgG antibody concentrations by sandwich ELISA in 23 patients with SLE and 30 controls who had participated in a cross-sectional 24-hour ambulatory BP study. We examined the association between anti-IsoLG IgG antibodies and BP measurements in patients with SLE and controls by Spearman Rho (rs) and linear regression analysis.Results: Serum anti-IsoLG IgG antibody concentrations were higher in patients with SLE than controls (P=0.007) and inversely associated with BP in SLE but not controls. In patients with SLE antibody concentrations were inversely associated with office (rs= -0.418) and diurnal systolic BP (rs= -0.421); the relationship was stronger among patients not taking anti-hypertensives (office: rs= -0.740, diurnal systolic BP: rs= -0.802) and every 20% increase in antibody concentration was associated with 10 mmHg decrease in 24-hour systolic BP (P=0.004).Serum anti-IsoLG IgG antibody concentrations are higher in patients with SLE than controls and are inversely associated with 24-hour BP measurements. Since IsoLGs promote hypertension, it is possible that in SLE, IsoLG antibodies could help clear these hypertensioninducing antigens.